Analysis of User Experience in Go Kreasi Application Using User Experience Questionnaire (UEQ) - Winengku, Audi Martya Putri; Utami, Haya; Sinaga, Suryaningsih; Sarungu, Cornelius Mellino (IJNMT (International Journal of New Media Technology), 2025)
This study aims to analyze the user experience of the Go Kreasi mobile application. The Go Kreasi application is a mobile application that provides tutoring services for students. The application was developed by PT. Ganesha Operation is still under development and used by 100 thousand users in Indonesia. The application has several features, including Visual, Audio, and Kinesthetic Ability Test (VAK), GO Assessment (GOA), Learning videos, Theory E-Books, Magic Books, Empathy, Racing, TOBK (Computer-Based Try Out), EPB, Leaderboard, and M3. [2] There are several complaints in the review of this application, such as color selection and icon placement. This makes the GO Kreasi application rating 2.7 out of 5 on the Apple Store and 2.3 out of 5 on the Play Store. A lot of the users said that the application is bad and that's the reason we wanted to do the research. This study aims to analyze the user experience of the Go Kreasi mobile application using the User Experience Questionnaire (UEQ). UEQ measures user experience based on six dimensions: satisfaction, efficiency, stimulation, aesthetics, clarity, and identity. The research method is an online survey of 58 respondents who answered 26 questions about the Go Kreasi application. The researchers conducted a demographic analysis of the respondents. Most of the respondents were aged 17 years old and were students at the high school level. The results of the study showed that the overall UX of the application is good. The results showed that the dimensions of clarity and identity had the highest scores, while the dimensions of efficiency had the lowest. However, some aspects need to be improved to improve the user experience. These aspects include the ease of use, the accuracy of the information, and the dependability of the application. The researchers concluded that the Go Kreasi application has the potential to be a useful tool for students. From the research, we expected the Go Kreasi application can be better and more evolved in the future.